Proposal Optimization Website of the Company PT Indoptune Net Manufacturing - Maulana Budiman, Muhammad Rizqi (Riviera Publishing, 2023)
Companies need digital marketing to achieve more profits compared to conventional marketing. One of the benefits of digital marketing is that it can reduce company marketing costs and connect and disseminate company-related information to Internet users worldwide. PT Indoneptune Net Mfg is a fishing gear industrial company that ventures jointly with Japan (Momoi Fishing Net Mfg. co., Ltd) and Indonesia. PT Indoneptune Net Mfg has its own digital marketing media: a website. However, currently, the company website could be more optimal because it does not contain information about the company or company products on the company website. This makes the author suggest optimizing the company's website because the entire world community can consume the information contained on the website. The information contained on the website makes customers more confident in the company's existence. It increases their confidence in deciding to purchase the company's products. The method that will be used is analyzing company data using the SWOT concept and improving the appearance of the company website using design thinking. Then, using the design thought method, a prototype will be created to conduct design testing using a usability test. This research shows that the score obtained for the company website design of PT Indoeptune Net Mfg was 93.8%, with a very high score category for all aspects.